The exchange rate pass-through to CPI and its components in oil-Exporting CIS countries - Vugar Rahimov; Nigar Jafarova; Fuad Ganbarov (Graduate Institute of International and Development Studies, 2017)
In this study, we explore the pass-through of exchange rate fluctuations to domestic CPI and its components for Azerbaijan, Kazakhstan and Russia. Using the data of 2003:Q1- 2016:Q2, we estimate a VAR model and find significant but incomplete pass-through in all sample countries. The accumulated pass-through to aggregate CPI within one year is 28 percent for both Azerbaijan and Kazakhstan; however the equivalent figure for Russia is 32 percent. According to our empirical findings the largest pass-through (ERPT) is observed in the non-food CPI in Azerbaijan and Kazakhstan, whereas in Russia the food prices demonstrate the greatest ERPT. Since the ERPT is an essential ingredient of price developments in sample countries, it should be assessed precisely and taken into account in monetary policy decisions and inflation forecasting.
Keywords: F31; E31; E52; C51; C52; 330; exchange rate pass-through; VAR model; disaggregated CPI; oil exporting countries